Physicochemical and phytochemical standardization of berries of Myrtus communis Linn. - Sabiha Sumbul (Journal of Pharmacy and Bioallied Sciences, 2012)
Purpose: Herbal medicines are gaining more and more attention all over the world due to their long historical clinical practice and less side effects. The major limitation with herbal medicines is that the lack of standardization technique. Initially, the crude drugs were identified by comparison only with the standard description available. Materials and Methods: Standardization of drugs means confirmation of its identity and determination of its quality and purity. The quality control standards of various medicinal plants, used in indigenous system of medicine, are significant nowadays in view of commercialization of formulations based on medicinal plants. The quality of herbal drugs is the sum of all factors, which contribute directly or indirectly to the safety, effectiveness, and acceptability of the product. Lack of quality control can affect the efficacy and safety of drugs that may lead to health problems in the consumers. Standardization of drugs is needed to overcome the problems of adulteration and is most developing field of research now. Therefore, there is an urgent need of standardized drugs having consistent quality. Results: The drug showed the presence of phyto-chemical constituents. Powdered drug was treated with different reagents and examined under UV light. Different reagents showed different colors of the drug at 2 wavelengths. The percentage of physiological active compounds viz. total phenolics, tannins, volatile oil, fixed oil, and alkaloids were also observed. Conclusion: Myrtus communis L. (Family: Myrtaceae) is one of the important drug being used in Unani system of medicine for various therapeutic purposes. In this study, an attempt has been made to study berries of M. communis from physico-chemical and phytochemical standardization point of view.